Mapping the relationship between education for sustainable development and climate change education: A bibliometric analysis - Angga Hadiapurwa; Saidatul Akmar Ismail; Dadi Mulyadi; Gema Rullyana; Diemas Arya Komara; Hafsah Nugraha (Universitas Sebelas Maret, 2026)
This study explores the relationship between Education for Sustainable Development (ESD) and Climate Change Education (CCE), focusing on their roles in addressing global environmental challenges. Through a bibliometric analysis of 468 scientific publications indexed in Scopus from 2015 to 2025, key themes such as sustainability, climate change, and the Sustainable Development Goals (SDGs) were identified as central to research in these fields. The findings emphasize the increasing importance of interdisciplinary approaches, emotional engagement, and the integration of ESD and CCE into curricula. The study also highlights the critical role of teacher education and the need for more sustainable practices in higher education, particularly in light of international student mobility. The research underscores the need to embed ESD and CCE into educational policies and frameworks to advance the global sustainability agenda. The bibliometric mapping reveals that publication output has grown sharply since 2020, with Walter Leal Filho, Maria Ojala, and Janet Richardson emerging as the most influential authors, while co-word analysis identifies transformative learning, systems thinking, and eco-anxiety as rapidly emerging research frontiers that bridge ESD and CCE.